(untitled) (Biological Sciences - PJSIR, 2022)
Three grades of mixed/complex fertilizers were field tested in wetland rice culture at Bangladesh Rice Research Institute (BRRI) farm during dry and wet seasons of the year 1992using randomized complete block design with a view to evaluate their effectiveness against straight fertilizers. Test varieties were BR3 and BRII for dry and wet seasons, respectively. Results implied that mixed/complex fertilizers were equally effective as straight fertilizers in increasing grain yield of rice. Mineral nutrition of and nutrient removal by rice plants were also almost similar irrespective of fertilizer sources.